Evaluation of CT features for differentiating consolidation pattern of pulmonary MALT lymphoma from pneumonic-type lung adenocarcinoma - Dong, Congsong; Xia, Peng; Qiu, Wenli; Dai, Zhenyu; Wang, Zhongqiu (Frontiers in Oncology, 2023)
In clinical practice, the consolidation pattern of pulmonary mucosa-associated lymphoid tissue (C-MALT) was often misdiagnosed as pneumonic-type lung adenocarcinoma (P-LADC). However, the mainstay of treatment and prognosis of these two diseases are different. The purpose of this study was to distinguish C-MALT from P-LADC by pre-treatment chest computed tomography (CT) features.: A total of 31 patients with C-MALT (15 men and 16 women; mean age, 61.1±11.2 years) and 58 patients with P-LADC (34 men and 24 women; mean age, 68.6±7.4 years) confirmed by pathology who underwent contrast-enhanced chest CT were retrospectively enrolled from September 2014 to February 2023. Detailed clinical and CT characteristics of the two groups were evaluated. Logistic regression analysis was used to assess the effectiveness of statistically significant variables in distinguishing C-MALT from P-LADC. Results: The average age of C-MALT was younger than P-LADC patients (p＜0.001). With regard to CT features, bronchiectasis within the consolidation was more common in the C-MALT group than the P-LADC group [83.87% (26 of 31) vs 20.69% (12 of 58), p<0.001]; whereas lymph nodes enlargement [75.86% (44 of 58) vs 9.68% (3 of 31), p<0.001] and pleural effusion [43.10% (25of 58) vs 19.35% (6 of 31), p=0.025] were more frequently observed in the P-LADC group than C-MALT group. The predictors with p<0.05 (age, bronchiectasis, lymph node enlargement, and pleural effusion) were used to construct a logistic regression model in discriminating C-MALT from P-LADC, the area under curve (AUC), positive predictive value (PPV), negative predictive value (NPV), specificity, sensitivity, and accuracy were 0.9555, 86.67%, 91.53%, 83.87%, 93.10%, and 89.89%, respectively. Conclusion: C-MALT and P-LADC have the differential clinical and CT features. An adequate understanding of these different characteristics can contribute to the early accurate diagnosis of C-MALT and provide appropriate therapeutic strategy.